The Role of the Madinah Market at the Time of the Prophet (Pbuh) - Omer, Spahic (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Role of the Madinah Market at the Time of the Prophet (Pbuh)